Distinct Spatio-Temporal Dynamics of Tumor-Associated Neutrophils in Small Tumor Lesions - Sody, Simon; Uddin, Mohib; Grüneboom, Anika; Görgens, André; Giebel, Bernd; Gunzer, Matthias; Brandau, Sven (Frontiers in Immunology, 2019)
Across a majority of cancer types tumor-associated neutrophils (TAN) are linked with poor prognosis. However, the underlying mechanisms, especially the intratumoral behavior of TAN, are largely unknown. Using intravital multiphoton imaging on a mouse model with neutrophil-specific fluorescence, we measured the migration of TAN in distinct compartments of solid tumor cell lesions in vivo. By longitudinally quantifying the infiltration and persistence of TAN into growing tumors in the same animals, we observed cells that either populated the peripheral stromal zone of the tumor (peritumoral TAN) or infiltrated into the tumor core (intratumoral TAN). Intratumoral TAN showed prolonged tumor-associated persistence and reduced motility compared to peritumoral TAN, whose velocity increased with tumor progression. Selective pharmacological blockade of CXCR2 receptors using AZD5069 profoundly inhibited recruitment of TAN into peritumoral regions, while intratumoral infiltration was only transiently attenuated and rebounded at later time points. Our findings unravel distinct spatial dynamics of TAN that are partially and differentially regulated via the CXCR2 signaling pathway.